Carbon fibre electrodes for ultra long cycle life pseudocapacitors by engineering the nano-structure of vertical graphene and manganese dioxides. (15th June 2021) - Sha, Zhao; Zhou, Yang; Huang, Feng; Yang, Wenmu; Yu, Yuyan; Zhang, Jin; Wu, Shuying; Brown, Sonya A.; Peng, Shuhua; Han, Zhaojun; Wang, Chun H.
Abstract: Critical to the applications of pseudocapacitors is the cycling performance of electrodes. Here, we present a new carbon fibre electrode enhanced by multilayer structure of vertical graphene (VG) and manganese dioxide (MnO2 ) to achieve a cycling performance at a very high areal capacitance (546.3 mF/cm 2 ) that outperforms most of the reported pseudocapacitors in the literature. Particularly, this multilayer electrode is able to retain 99.3% of its initial capacitance after 10, 000 cycles at scan rate of 200 mV/s. The retention ratio is significantly higher than the state-of-art value. In addition, this electrode shows excellent rate performance (75.4% capacitance retention for current density from 1 to 10 mA/cm 2 ). This exceptionally high stability at high capacitance and rate performance originates from the multilayer electrode's effectiveness in self-replenishing the degraded MnO2 in the outer layer. The microcracks and micro holes induced in the VG layer by electrical charge/discharge cycling enable the inner layer MnO2 to progressively participate in the redox reaction. Results from energy dispersive spectroscopy, X-ray photoelectron, and Raman spectroscopy confirm the self-replenishing mechanism responsible for the exceptionally stable performance. The new multilayer electrode designed herein provides a new route for improving the cycling performance of pseudocapacitors. Graphical abstract: Image 1 Highlights: A multilayer electrode was prepared by interleaving vertical graphene and MnO2 . Defects in graphene activated inner active material for full redox reaction. This new electrode offers a novel self-replenishing capability. The electrode offers ultrahigh capacitance retention of 99.3% after 10, 000 cycles.